Cardiovascular mortality and risk behaviours by degree of urbanization before, during and after the economic crisis in Spain - Almudena Moreno-Lostao; Juan M. Guerras; Lourdes Lostao; Luis de la Fuente; David Martínez; Fernando Rodríguez-Artalejo; Enrique Regidor (BMC, 2019)
Abstract Background To estimate the relationship of the degree of urbanization to cardiovascular mortality and to risk behaviours before, during and after the 2008 economic crisis in Spain. Methods In three areas of residence - large urban areas, small urban areas and rural areas - we calculated the rate of premature mortality (0-74 years) from cardiovascular diseases before the crisis (2005-2007), during the crisis (2008-2010 and 2011-2013) and after the crisis (2014-2016), and the prevalence of risk behaviours in 2006, 2011 and 2016. In each period we estimated the mortality rate ratio (MRR) and the prevalence ratio, taking large urban areas as the reference. Results In men, no significant differences were observed in mortality between the two urban areas, while the MRR in rural areas went from 0.92 [95% confidence interval, 0.90-0.94) in 2005-2007 to 0.94 (0.92-0.96) in 2014-2016. In women, no significant differences were observed in mortality between the rural and large urban areas, whereas the MRR in small urban areas decreased from 1.11 (1.08-1.14) in 2005-2007 to 1.06 (1.02-1.09) in 2014-2016. The rural areas had the lowest prevalence of smoking, obesity and physical inactivity in men, and of obesity in women. No significant differences were observed in smoking or physical inactivity by area of residence in women. Conclusion The pattern of cardiovascular mortality by degree of urbanization was similar before and after the crisis, although in women the excess mortality in small urban areas with respect to large urban areas was smaller after the crisis. The different pattern of risk behaviours in men and women, according to area of residence, could explain these findings.